STRATEGI DINAS TENAGA KERJA (DISNAKER) KOTA PEMATANGSIANTAR DALAM MENANGGULANGI PENGANGGURAN - Esther Imanuela Simanjuntak; Harapan Tua RFS (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Unemployment is one of the main problems that are closely related to economic growth. Unemployment is generally caused by the fact that the labor force is not proportional to the number of jobs available. The purpose of this study is to clarify the strategy of the Pematangsiantar City Manpower Office in tackling unemployment in the covid-19 pandemic era and to find out what factors affect the Pematangsiantar City Manpower Office in tackling the unemployment problem in the covid-19 pandemic era. The theoretical concept used in this research is the strategy theory proposed by Ellitan and Anatan (2008:9) to measure the strategies that have been set in organizations or companies, such as technology strategies, innovation strategies, and operations strategies. This study uses a qualitative research method with a descriptive approach. The data analysis technique used Nasution's theory (2000: 128). The results of this study indicate that the strategy of the Pematangsiantar City Manpower Office in tackling unemployment in the era of the covid-19 pandemic has not run optimally due to limited funds owned by the Manpower Office and limited human resources.